Financial Literacy and Its Influencing Factors Among Students in Lalitpur - Thapa, Shyam Kumar; Maharjan, Munita (Khwopa Journal, 2025)
This study examines the level of financial literacy among college students in Lalitpur Metropolitan City and investigates how financial behavior, financial influence, and financial attitude impact their financial literacy. Drawing on Human Capital Theory and Financial Socialization Theory, the research employs a quantitative approach using survey data from 250 undergraduate and graduate students selected through snowball sampling. Data was collected via structured questionnaires and analyzed using descriptive statistics and multiple regression. The results indicate that while students exhibit high knowledge of banking services, their understanding of insurance, credit, and general financial concepts is relatively low. Financial behavior was found to significantly influence financial literacy, whereas financial attitude and financial influence did not have a statistically significant impact. The findings emphasize the importance of practical financial behaviors over attitudinal and social factors in shaping financial knowledge and suggest the need for targeted educational interventions to improve financial capability among Nepalese youth.